1997
DOI: 10.1002/(sici)1097-0215(19970620)74:3<275::aid-ijc7>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin expression in human epithelial ovarian cancer and normal ovary

Abstract: The ovarian surface epithelium (OSE) is the origin of the majority of human ovarian cancers. These adenocarcinomas are characterized by initial local growth followed by spreading into the peritoneal cavity at later stages of tumor progression. The cell-adhesion molecule E-cadherin (E-cad) plays an important role in maintaining tissue integrity. Disappearance or impaired function of E-cad have often been associated with tumor formation and invasion in vivo and in vitro. The cell-specific expression of E-cad was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 0 publications
3
42
0
1
Order By: Relevance
“…However, in the same study, it was shown that neither E‐cadherin (5) nor claudin‐4 are expressed in the normal OSE. On the contrary, we and others have shown up regulation of mRNA and corresponding proteins in EOC compared to surface‐OSE (12–19). In addition, over‐expression of claudin‐3 and claudin‐4 in cultured OSE rendered a more invasive cell, while blocking claudin‐3 and claudin‐4 production in EOC actually reduced invasiveness (20).…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, in the same study, it was shown that neither E‐cadherin (5) nor claudin‐4 are expressed in the normal OSE. On the contrary, we and others have shown up regulation of mRNA and corresponding proteins in EOC compared to surface‐OSE (12–19). In addition, over‐expression of claudin‐3 and claudin‐4 in cultured OSE rendered a more invasive cell, while blocking claudin‐3 and claudin‐4 production in EOC actually reduced invasiveness (20).…”
Section: Introductionmentioning
confidence: 54%
“…OSE is also found lining small cyst formations in the ovarian stroma, where the tumours are first encountered during benign or early stages of the disease (1), (3), (22). The OSE within cysts expresses E‐cadherin, claudin‐3 and claudin‐4, and has a more epithelial‐like morphology than surface‐OSE, which lack these typical epithelial markers (12), (13), (18). OSE seems to go through mesothelial–epithelial conversion in the ovarian stroma before transformation into tumour cells of quite diverse and heterogenic histology with main subgroups, such as serous, mucinous, endometrioid, clear cell and undifferentiated adenocarcinomas of the ovary (22).…”
Section: Discussionmentioning
confidence: 99%
“…This study further analyzes morphologic and biochemical features of ovaries considered at high risk for developing ovarian carcinoma using immunohistochemical expression patterns of the following markers: CA‐125, p53, Mib‐1, Bcl‐2, and E‐cadherin. All of these markers have been reported previously to show significant differences in expression in normal/benign ovarian surface epithelium compared with ovarian carcinoma tissues 13–20. Our hypothesis was that expression patterns of these markers in high‐risk ovaries may deviate from normal ovaries and assume a pattern similar to that seen in carcinomas.…”
mentioning
confidence: 85%
“…Similar to other members of the cadherin family, E‐cadherin binds to the actin‐based cytoskeleton by a group of proteins called catenins, forming the zonula adherens 29, 39. Increased E‐cadherin expression has been demonstrated in both benign and malignant ovarian epithelial neoplasms 53, 54. In the normal ovary, E‐cadherin expression is either absent or present inconsistently on the ovarian surface but is increased in surface invaginations and epithelial inclusion cysts 53–55.…”
Section: Discussionmentioning
confidence: 99%
“…Increased E‐cadherin expression has been demonstrated in both benign and malignant ovarian epithelial neoplasms 53, 54. In the normal ovary, E‐cadherin expression is either absent or present inconsistently on the ovarian surface but is increased in surface invaginations and epithelial inclusion cysts 53–55. The latter are the sites of frequent metaplastic and dysplastic changes 56–59.…”
Section: Discussionmentioning
confidence: 99%